2011
DOI: 10.1021/tx1004437
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Genotoxicity of a Pyrrolidine Substituted Arylindenopyrimidine As a Potent Dual Adenosine A2A/A1 Antagonist by Minimizing Bioactivation to an Iminium Ion Reactive Intermediate

Abstract: 2-Amino-4-phenyl-8-pyrrolidin-1-ylmethyl-indeno[1,2-d]pyrimidin-5-one (1) is a novel and potent selective dual A(2A)/A(1) adenosine receptor antagonist from the arylindenopyrimidine series that was determined to be genotoxic in both the Ames and Mouse Lymphoma L5178Y assays only following metabolic activation. Compound 1 was identified as a frame-shift mutagen in Salmonella typhimurium tester strain TA1537 as indicated by a significant dose-dependent increase in revertant colonies as compared to the vehicle co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…Both systems were equipped with an electrospray ionization source operated in the positive ion mode. Accurate mass measurements using LTQ/Orbitrap were obtained by modification of a previously (Lim et al, 2007) or internal mass calibration by infusion of 10 pg/ml of tamoxifen (Lim et al, 2011). The source parameters were tuned for maximum sensitivity by infusion of 5 or 10 ng/ml canagliflozin in 50% acetonitrile/50% water directly into the mobile phase.…”
Section: Preparation Of Biologic Samples For Metabolite Profilingmentioning
confidence: 99%
“…Both systems were equipped with an electrospray ionization source operated in the positive ion mode. Accurate mass measurements using LTQ/Orbitrap were obtained by modification of a previously (Lim et al, 2007) or internal mass calibration by infusion of 10 pg/ml of tamoxifen (Lim et al, 2011). The source parameters were tuned for maximum sensitivity by infusion of 5 or 10 ng/ml canagliflozin in 50% acetonitrile/50% water directly into the mobile phase.…”
Section: Preparation Of Biologic Samples For Metabolite Profilingmentioning
confidence: 99%
“…Instead, the most commonly utilized approach is to capture the reactive intermediate with a trapping agent, leading to formation of stable adducts of reactive metabolites that can be detected and characterized using LC-MS/MS techniques [4][5][6]. These methods have been extensively applied to efforts in the minimization of bioactivation for lead compounds at the drug discovery stage [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…MDF processing of high resolution full MS data set provided unambiguous identification of both hard and soft reactive metabolites. A different approach was presented by Lim et al in their work of minimizing bioactivation of a drug candidate, in which S9 incubation in the presence of GSH and CN, along with their stable isotope analogues, was subject to HR-MS and isotope pattern dependent MS n acquisition on Orbitrap MS [11]. Mitchell et al used a peptide consisting of eleven amino acids including a terminus GSH and additional nucleophilic residues (e.g., lysine) for simultaneously trapping of both soft and hard electrophiles [31].…”
Section: Introductionmentioning
confidence: 99%
“…Case examples linking α-carbon oxidation of cyclic tertiary amines and iminium ions to covalent binding have been reported in the literature, 7−10 which include a report of genotoxicity caused by covalent modification of DNA. 11,12 These results raise the possibility that metabolic bioactivation of rimonabant could have toxicological consequences, especially in view of the key role played by reactive metabolites in the toxicity of many other drugs and foreign compounds. 13 In support of this possibility, recently it has been found that rimonabant exhibits potentiated in vitro toxicity to human liver derived THLE cell lines, which expressed P450 3A4 compared to THLE cells that expressed no P450 activity.…”
Section: ■ Introductionmentioning
confidence: 99%